2015
DOI: 10.1109/tasc.2014.2360139
|View full text |Cite
|
Sign up to set email alerts
|

Liquid Nitrogen Tests of a Torus Coil for the Jefferson Lab 12-GeV Accelerator Upgrade

Abstract: A magnet system consisting of six superconducting trapezoidal racetrack-type coils is being built for the Jefferson Lab 12GeV accelerator upgrade project. The magnet coils are wound with Superconducting Super Collider-36 NbTi strand Rutherford cable soldered into a copper channel. Each superconducting toroidal coil is force cooled by liquid helium which circulates in a tube which is in good thermal contact with the inside of the coil. Thin copper sheets are soldered to the helium cooling tube and wrap round th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…Upon arrival, each coil was inspected, instrumented with temperature sensors and strain gauges, and underwent a cool down test to 80 K (see Fig. 30) to assess the robustness of the coil's electrical insulation and its structural integrity, as well as to test the efficacy of the employed conduction cooling method [36]. Table XXVII summarizes the results obtained from the 80 K test, data extrapolation to 4 K, and comparison with the results obtained from the finite element analysis.…”
Section: K Cold Test and Cryostatingmentioning
confidence: 99%
“…Upon arrival, each coil was inspected, instrumented with temperature sensors and strain gauges, and underwent a cool down test to 80 K (see Fig. 30) to assess the robustness of the coil's electrical insulation and its structural integrity, as well as to test the efficacy of the employed conduction cooling method [36]. Table XXVII summarizes the results obtained from the 80 K test, data extrapolation to 4 K, and comparison with the results obtained from the finite element analysis.…”
Section: K Cold Test and Cryostatingmentioning
confidence: 99%
“…The 12 GeV team was thus encouraged to explore alternatives. The team reviewed the pros and cons of a 4 K test versus an 80 K test and concluded that the 'high' and 'medium' category risks could be sufficiently mitigated by subjecting each torus coil to an 80 K test by flowing liquid nitrogen through each coil's cooling tubes [21]. An extract from the team's review report is provided in table 5.…”
Section: Risk Mitigation Strategy-sensors and Technologymentioning
confidence: 99%
“…After finished coils passed their receipt inspection at JLab, they were fully instrumented with temperature sensors and strain gages in preparation for an 80 K cold test [9], which was part of the Cryostat Factory task. The aim of this test was to verify the integrity of the coil's electrical insulation at cryogenic temperatures as well as to confirm the efficacy of the CCM's conduction cooling methodology.…”
Section: Cryostat Factorymentioning
confidence: 99%